Characterization of size distribution and markers for mosquito extracellular vesicles - Rey-Cadilhac, Félix; Rachenne, Florian; Marquant, Antonin; Kee Him, Josephine Lai; Ancelin, Aurélie; Foisor, Veronica; Morille, Marie; Lyonnais, Sébastien; Cazevieille, Chantal; Missé, Dorothée; Pompon, Julien (Frontiers in Cell and Developmental Biology, 2025)
Extracellular vesicles (EVs) are non-replicative, cell-derived membranous structures secreted by potentially all eukaryotic cells, playing a crucial role in intercellular communication. The study of EVs requires approaches and tools, which have predominantly been developed for mammalian models. Here, we undertook a multimodal characterization of mosquito EVs to provide a technical and knowledge foundation for their study. First, using a cell line model from Aedes aegypti and applying multiple analytical technologies (i.e., NTA, TEM, cryo-EM, and AFM), we observed that mosquito EVs range from 20 to 500 nm in diameter and that a majority are smaller than 100 nm. Second, we showed that smaller EVs are secreted in mosquito saliva. Third, we evaluated the capacity of differential centrifugation and size exclusion chromatography to separate mosquito EVs, revealing the strengths and weaknesses of each technology. Finally, we identified a mosquito homolog of CD63 as an extravesicular marker and the mosquito syntenin as a putative luminal marker. Overall, our results promote the development of tools and approaches for the study of mosquito EVs.